COVID-19 experiences of small-scale fishing households: The case of Lake Victoria, Kenya - Okronipa, Harriet; Bageant, Elizabeth R.; Baez, Jazmin; Onyango, Horace Owiti; Aura, Christopher Mulanda; Fiorella, Kathryn Joan (Frontiers in Sustainable Food Systems, 2023)
ABSTRACT The impact of COVID-19 on small-scale fishing communities is of great concern given the importance of aquatic foods in trade, nutrition and livelihoods. Using a case study of Lake Victoria, augmented by published literature, we examine the socioeconomic dynamics and severity of COVID-19 impacts on Kenyan fishing communities. A household level questionnaire was administered through phone interviews on a monthly basis from June 2020 to May 2021, including a focus group discussion in July 2021. We find that multifold fear of COVID-19 infection and control measures were present and varied across case rates and stringency of control measures. Fishers and traders reported being affected by disease control measures that limited market access and their ability to fish overnight. In spite of these worries, and contrary to what has been reported in the published literature regarding impacts observed in the early months of the pandemic, we see stable participation in fishing and fish trading over time despite the pandemic.. Food insecurity was high before and during the COVID-19 pandemic, but did not substantially shift with the pandemic. Our findings suggest that Kenyan fishing and fish trading households adopted diverse strategies to cope and balance generating income to provide for their families and staying safe. Our results underscore the need to understand ways in which acute pandemic impacts evolve over time given that effects are likely heterogeneous across small-scale fishing communities.